Open Controller for Distributed Instrumentation Systems - Viegas, Vítor (2013)
The paper presents a controller designed to be highly interoperable in the context of distributed instrumentation systems. Interoperability is achieved by adopting strong standards – the IEEE 1451.1 Std to be more precise – and by using cross-platform, manufacturer-independent technologies such as Web Services. The 1451.1 Std contributes with its information model to represent data and organize functionalities through a well-defined hierarchy of objects. Web Services are used to implement both communication models, the client/server model for one-to-one communications, and the publish/subscribe model for one-to-many communications. Being supported by all the major software companies around the world, Web Services have the chance to become the first wide-used middleware solution and the answer for many interoperability problems. The controller was developed using the .NET Framework and tested in the Windows XP operating system.